The influence of embedded optical fiber on the internal structure of polymer composite material - Kosheleva, N.A.; Serovaev, G.S. (Perm Federal Research Centre Journal, 2021)
In this work the samples made of polymer composite materials with embedded optical fibers were studied. The diameter of the optical fiber is comparable to the thickness of the layer of the composite material. So, the internal structure of the source material may be distorted in the vicinity of the optical fiber because of optical fiber embedment. Consequently, the formation of technological defects poses a threat to the integrity of the source material. Cross-sectional micrographs of various types of composite materials in the vicinity of the embedded optical fiber were obtained in the study. For a unidirectional composite material the formation of a resin pocket when the optical fiber is embedded perpendicular to the direction of the reinforcing fibers and its absence when the optical fiber is embedded parallel to the direction of the reinforcing fibers is confirmed. The analysis of images of woven polymer composite materials with twill weave did not reveal significant distort ons of the internal structure of the source material. Recommendations are given for preliminary treatment (polishing) of fiber-glass and carbonfiber reinforced plastic specimen surfaces.In contrast to the known results on the significant influence of the layering scheme on the efficiency of optical fibers embedment into composite materials, the data obtained in this study also indicate the effect of the material of the reinforcing fibers and the type of reinforcement on the quality of embedding optical fibers. These factors should be considered when designing and creating structures with embedded fiber-optic sensors.